Oral Health Impact Profile in elderly Chileans in southern Chile. - Matías Yobánolo-Hoffmann; Javiera Valentin-Hoyos; Pedro Christian Aravena (Universidad de Concepción., 2015)
Aim: To evaluate the impact of oral health on the quality of life of elderly patients (EP) in the public health system of Valdivia, Chile in 2015. Methods: A descriptive study was conducted using the "Oral Health Impact Profile Spanish version" (OHIP-14Sp), in a population of 387 EP (71.8±7.5 years old; 53% women). The impact of oral health on the quality of life was determined by the mean scale score that ranged beween 0 points (good quality of life) and 56 points (poor quality of life). In addition, oral health problems reported by EP population as having a greater influence on their quality of life were also included in this study. Results: The mean score of OHIP-14Sp was 20.1±7.6 points. Items showing problems more frequently associated with quality of life were: "toothache" (32.8%), "appearance of the teeth" (32.8%), "sensitive teeth" (32.3%) and "difficulty for chewing food" (25.8%). Conclusion: The impact of oral health on the quality of life of the EP population was considered low when compared to the median score of OHIP-14Sp. Functional and aesthetic aspects showed the highest impact on the quality of life of EP in the city of Valdivia.